Bioremediations Technologies on Wastewater Treatment: Opportunities, Challenges and Economic Perspective - Dewi Rosanti; Yudha Gusti Wibowo; Muhammad Safri; Anis Tatik Maryani; Bimastyaji Surya Ramadhan (Universitas PGRI Palembang, 2020)
Bioremediation is one of high value and low-cost technologies to solve environmental degradation. In this paper, we made a systematic review of bioremediation utilization for wastewater treatment. This paper aims to describe the current bioremediation technologies, potential microorganisms involved, recent bioremediation treatment research to solve environmental damage and economic comparation of bioremediations processes. The regulatory of heavy metals limitation in drinking water is also reported in this paper. Thus, this paper described comprehensive information on bioremediation in the world and this future research direction.